2019
DOI: 10.3892/ol.2019.11076
|View full text |Cite
|
Sign up to set email alerts
|

Expression and function of long non‑coding RNA LINC01420 in thyroid cancer

Abstract: The Human Genome Project revealed that >90% of the human genome was found to transcribe non-coding RNAs, including micro RNAs and long non-coding RNAs (lncRNAs). lncRNAs have been identified to play a crucial role in cancer progression. Thyroid cancer (TC) is a common type of endocrine cancer; however, the functional roles of lncRNAs in TC have yet to be fully elucidated. The present study investigated whether LINC01420 was upregulated in TC tissues, compared with normal thyroid tissues, and the results sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…22 Their abnormal expression in cancer patients may cause the normal physiological process of cells to get out of control and eventually lead to the development and progression of tumors. 23 This study explored TC, which is a common malignant endocrine tumor, 24 so we analyzed the potential regulatory value of LncRNAs through clinical samples and cell functional experiments in vitro. PVT1 has been confirmed to function as a tumor promoter in TC, but its molecular mechanism remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…22 Their abnormal expression in cancer patients may cause the normal physiological process of cells to get out of control and eventually lead to the development and progression of tumors. 23 This study explored TC, which is a common malignant endocrine tumor, 24 so we analyzed the potential regulatory value of LncRNAs through clinical samples and cell functional experiments in vitro. PVT1 has been confirmed to function as a tumor promoter in TC, but its molecular mechanism remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Linc01420 is upregulated in nasopharyngeal cancer and is positively associated with tumor metastasis and an unfavorable prognosis [59]. Linc01420 also facilitates cell proliferation and migration in melanoma [60], promotes pancreatic cancer development via targeting KRAS [61], and accelerates cell cycle progression and cell proliferation in thyroid cancer [62]. Proteomics analysis showed that the 7 kDa micropeptide, non-annotated P-body dissociating micropeptide (NoBody), was translated from LINC01420/LOC550643 in leukemia K562 and breast cancer MDA-MB-231 cells (Fig.…”
Section: Nobodymentioning
confidence: 99%
“…Furthermore, LOC550643 knockdown could suppress pancreatic cancer cell growth and invasion capability through releasing miR-494-3p sponging. Relevant studies have also investigated the role of LOC550643 in thyroid cancer, revealing significantly higher levels of LOC550643 expression in thyroid cancer cells and that LOC550643 knockdown inhibited cancer cell growth by impairing cell cycle progression ( Luo et al, 2020 ). By contrast, Konina et al (2019) reported an opposite role, in which LOC550643 inhibited melanoma cell migration ability but did not influence cell growth.…”
Section: Discussionmentioning
confidence: 99%